PP1 forms an active complex with TLRR (lrrc67), a putative PP1 regulatory subunit, during the early stages of spermiogenesis in mice. - Rong Wang (Public Library of Science (PLoS), 2011)
Mammalian spermatogenesis is a highly regulated developmental pathway that demands dramatic rearrangement of the cytoskeleton of the male germ cell. We have described previously a leucine rich repeat protein, TLRR (also known as lrrc67), which is associated with the spermatid cytoskeleton in mouse testis and is a binding partner of protein phosphatase-1 (PP1), an extremely well conserved signaling molecule. The activity of PP1 is modulated by numerous specific regulators of which TLRR is a candidate. In this study we measured the phosphatase activity of the TLRR-PP1 complex in the adult and the developing mouse testis, which contains varying populations of developing germ cell types, in order to determine whether TLRR acts as an activator or an inhibitor of PP1 and whether the phosphatase activity of this complex is developmentally regulated during spermatogenesis. Additionally, we assayed the ability of bacterially expressed TLRR to affect the enzymatic activity of PP1. Furthermore, we examined phosphorylation of TLRR, and elements of the spermatid cytoskeleton during the first wave of spermatogenesis in the developing testis. We demonstrate here that the TLRR complex is associated with a phosphatase activity in adult mouse testis. The relative phosphatase activity of this complex appears to reach a peak at about 21 days after birth, when pachytene spermatocytes and round spermatids are abundant in the seminiferous epithelium of the mouse testis. TLRR, in addition to tubulin and kinesin-1B, is phosphorylated during the first wave of spermatogenesis. These findings indicate that the TLRR-PP1 complex is active prior to translocation of TLRR toward the sperm flagella and that TLRR, and constituents of the spermatid cytoskeleton, may be subject to regulation by reversible phosphorylation during spermatogenesis in murine testis.